PEMBERDAYAAN MASYARAKAT DENGAN PELATIHAN PEMBUATAN SABUN CUCI PIRING DI DESA HILIGAMBUKHA KECAMATAN LAHUSA - Haratoli Buulolo; Thomas Dermawan Buulolo; Menni Asria Duha; Pengalaman Hulu; Riska J. R. W Telaumbanua; Grace Mariana Gulo; Krisdayanti Gaurrifa; Guslina Laia; Aswandi Zamili; Niaswati Wau; Desniar Loi; Erasma Fitilia Zalogo (Universitas Nias Raya, 2025)
Community empowerment plays an important role in improving the capacity, skills, and independence of rural communities. One of the effective approaches is through training programs that equip people with practical skills and entrepreneurial opportunities. This article focuses on a community empowerment program carried out in Hiligambukha Village through dishwashing soap-making training. The activity was designed not only to encourage creativity, innovation, and economic independence at the village level. The implementation method consisted of several stages, including preparation, socialization, delivery of theoritical material, live demonstration, participant practice, evaluation, and post-training mentoring. The results of the training showed significant improvement in both knowledge and skilss. Participants successfully produced dishwashing soap independently and demonstrated the ablity to follow production procedures correctly. Beyond meeting household needs, the training opened oppurtunities for participants to market their products and generate additional income. The findings indicate that such training contributes to multiple aspects of community empowerment. It not only provides economic benefits, such as cost savings and income generation, but also fosters self-reliance, teamwork, and enterpreneurial spirit among participants. Therefore, this program can serve as a model for other villages aiming to develop community-based economic initiatives.